Pledges of Jewish allegiance conversion, law, and policymaking in nineteenth- and twentieth-century Orthodox responsa - Ellenson, David Harry; Gordis, Daniel (Stanford, Calif. : Stanford University Press, 2012)
Introduction : Who is a Jew? What is a Jew? : Jewish identity, Jewish status, and the challenge of conversion -- Conversion in Jewish tradition : an introduction to the classical sources -- Trends in nineteenth- and early-twentieth-century German Orthodox responses to conversion and intermarriage -- Hungarian and Central European writings on conversion and intermarriage -- Europe and the United States in the modern period -- Israel : conversion to Judaism in a Jewish society
Introduction : Who is a Jew? What is a Jew? : Jewish identity, Jewish status, and the challenge of conversion Conversion in Jewish tradition : an introduction to the classical sources Trends in nineteenth- and early-twentieth-century German Orthodox responses to conversion and intermarriage Hungarian and Central European writings on conversion and intermarriage Europe and the United States in the modern period Israel : conversion to Judaism in a Jewish society.